Probing into the properties of B4C reinforced nickel phosphorus-based nanocomposite coating - Osama Fayyaz; Moinuddin M. Yusuf; Sara Bagherifard; M.F. Montemor; R.A. Shakoor (Journal of Materials Research and Technology, 2022)
Nickel-based coatings are well known for their good corrosion resistance performance. However, these materials suffer from inferior mechanical properties that limit their wider application. This work investigates the synthesis, and performs an exhaustive characterization, of Ni–P–B4C nanocomposite coatings developed through conventional electrodeposition using a modified Watts bath. The study examines the effect of an increase in the concentration of boron carbide nanoparticles (BCNPs) on the structural, morphological, topographical, mechanical and electrochemical properties of the nanocomposite coating. Vickers microhardness tester and nanoindentation technique were utilized to elucidate the role of BCNPs in modifying the mechanical response of nanocomposite coatings. Furthermore, corrosion resistance of the nanocomposite coatings was investigated through d.c potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). Comparison of the properties of the developed coatings revealed the remarkable improvement in the properties of Ni–P–B4C nanocomposite coatings when compared to the bare mild steel substrate and the Ni–P coatings. The enhanced corrosion resistance and superior mechanical properties of Ni–P–B4C nanocomposite coatings make them attractive for many industries. Based upon the experimental findings, a possible mechanism for the synthesis and improved corrosion resistance of Ni–P–B4C nanocomposite coatings was also proposed.